Model pembelajaran classroom community partnership (CCP) dalam pembelajaran PPKn - Lisye Salamor (Inovasi Kurikulum, 2015)
Classroom Learning Community Partnership Model (CCP) as an innovative learning product useful in integrating a variety of learning resources in civic education at primary schools. Research and development method in the process of developing the model, has proven successful in improving the social cognitive skills with parents involvement as a source and models of learning in the learning process.